Real-Time Environmental Gamma Dose Rates Measurement and Evaluation of Annual Effective Dose to population of Shahbag Thana, Dhaka, Bangladesh - Tazmin, Shamsad; Rahman, Dr. Mohammad Sohelur; Yeasmin, Selina; Ahsan, Dr. M. Habibul; Mahfuzzaman, Md. (International Journal of Scientific Research and Management (IJSRM), 2018)
Background: In this study, environmental gamma radiation dose rates were measured in the area of Shahbag Thana under Dhaka city, Bangladesh.Aim of the study: This kind of study is required to detect the presence of natural and artificial radionuclides (if any) releasing from nuclear facilities in the country or from neighbouring countries. Materials and Method: The measurement was performed using a digital portable Gamma-Scout detector. The digital portable Gamma-Scout detector was placed at 1 meter above the ground on tripod and data acquisition time for each monitoring point (MP) was 1 hour. Total 27 MPs were selected for collection of gamma-ray dose rate in the outdoor environment of Shahbag Thana. The measurements were performed during light day from January to September 2017. The MPs were marked-out using Global Positioning System (GPS) navigation. The GP Sreading of the sampling locations were varied from E: 90˚23'32.94" to E: 90˚24'31.32" and from N:23˚44'19.38" to N: 23˚43'24.3". Results: The measured dose rates due to natural radionuclides were ranged from 0.085 ± 0.0245µSv.h-1 to 0.190526 ± 0.081886 µSv.h-1 with an average of 0.145265 ± 0.025192 µSv.h-1.The annual effective dose to the population from outdoor environmental gamma radiation was varied from0.104244 ± 0.030041 mSv  to 0.233661085 ± 0.100425 mSv. The range of dose rate and annual effective dosedue to outdoor environmental gamma radiation is lower than some countries like India, Sweden, China, CzechRepublic, Italy and higher than Canada, Turkey, Indonesia, Belgium, Albania, New Zealand and some other counties. Conclusion: From this study, it was observed that there is no burden of population exposure due to man-made sources. Therefore, it can be concluded that adequate safety and radiation protection of radiological facilities had been ensured which is required for minimizing of unnecessary exposure to populations from man-made sources. The estimated mean annual effective dose found in this study is not expected to contribute significant additional hazard from the radiological health point of view.